THE MEDIATING EFFECTS OF BRAND LOVE ON REVISIT INTEREST A META ANALYSIS - Wijaya, Nyoman; Giantari, I; Sukaatmadja, I; Ekawati, Ni (Faculty of Economic and Business, University of Pasundan, 2024)
Research on Brand Love has an important influence on interest in returning visits, and reveals various benefits for tourist attraction managers. This study aims to collect empirical evidence about the effectiveness of Brand Love in attracting tourists. A meta-analysis method, with calculated the effect size 33 publications from the results of the study between 2019-2023. The results show that Brand Love mediation in attracting tourists has a positive and high influence on return visits to a tourist attraction. Based on the analysis of mediator variables related to instructional characteristics, there were significant differences in the variables of the type of visit, the characteristics of tourists, and the type of Brand Love. However, moderator variables related to methodological characteristics did not have a significant moderating influence on revisiting interest. This research contributes to marketing management, in winning the interest of tourists to revisit a tourist spot through the role of brand love.